The Role of the Socio-Drama Type Role Playing Learning Model in Social Studies Learning on Student Creativity at SMPN 1 South Tangerang City - Danang Seta Widjaya; Faqih Samlawi; Dina Siti Logayah (Dinasti International Journal of Education Management And Social Science, 2024)
The role-playing learning model is a learning model that is known in the world of education to train students' skills. The aim of this research is to discuss the role of the role-playing learning process which creates a socio-drama performance in responding to students' creative achievements after learning takes place. This research method uses a quantitative descriptive approach. The sample for this research was taken from students in class VIII 6 of SMPN 1 South Tangerang City with a total of 38 students in that class. The results of this research obtained a positive influence from students in assessing the results of the scope of student creativity according to the indicators that were met, namely fluency, flexibility, originality and elaboration. This research obtained the percentage of implementation of the role-playing learning model at SMPN 1 South Tangerang City, namely variable X 45.79 and ranging in the range 37-48 in the medium category. This also makes the role-playing learning model a recommended learning model for social studies subjects. Student creativity also has a positive impact, such as students being able to interact with groups and students also being able to create drama scripts according to the ideas and ideas that students express.  The conclusion of this research is that the role-playing learning model is a model that can be used in learning as a benefit in increasing students' creativity in completing tasks given by the teacher.